Native American Youth Citizen Scientists Uncovering Community Health and Food Security Priorities. Issue 1 (January 2020) - Kim, Katherine K.; Ngo, Victoria; Gilkison, Grant; Hillman, Lisa; Sowerwine, Jennifer
Citizen science based on principles of community-based participatory research involves the co-creation of research among citizens and professional researchers in substantive aspects of scientific inquiry including equitable contributions to governance, research questions, data collection, analysis, application of findings, and dissemination. This article reports on a citizen science project conducted by 12 youth in the Karuk Tribe collaborating with university scientists. The youth participated in a research leadership development program conducted in their community located in rural/remote northern California. The youth led a community health and food security assessment survey using a mobile application tool (n = 212). They uncovered community concerns about the health of residents and healthfulness of food choices in schools, as well as a significant difference related to confidence in making healthy food choices between those who are and are not physically active. The Tribe applied the study findings with youth in alignment with cultural values and practices investing in developing community gardens, improving school food quality, and promoting native food practices that incorporate physical activities such as hiking, gathering, and preserving food. This study offers lessons for research collaborations among citizen scientists from communities underrepresented in health research and university scientists.